Fatores determinantes no resultado do tratamento do empiema pleural em crianças: drenagem pleural simples ou videotoracoscopia? Ensaio clínico controlado - Hasimoto, Fabio Nishida [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The empyema have been treated in various ways, from the serial thoracocentesis, exclusive thoracic drainage, drainage and fibrinolytics, infusion thoracotomy and decortication for cavity cleansing to drainage through videothoracoscopy (VATS). Although drainage is a quite old method, it is very effective, depending on the stage of empyema. The VATS even being more invasive, since requires general anesthesia, is resolute in most stages of empyema. To analyze cases of parapneumonic pleural empyema in children undergoing simple drainage or early VATS in our service in order to determine the conclusive factors in a favorable treatment outcome. Prospective controlled trial that evaluated age, gender, time of diagnosis, aspect of the fluid, pathogens, type of treatment (simple chest tube drainage or early VATS), drainage time, need for reintervention, need to change antibiotics and hospitalization time. Fifty-four patients aged seven months old to 10 years old with a diagnosis of empyema were analyzed. Male gender was predominant (54%), right hemithorax was the most affected (28 patients) and the duration of clinical symptoms ranged from one to 30 days. Thirty- two patients were previously treated with antibiotics and in 22% of cases bacterioscopy and / or culture were positive and the most common agent was Streptococcus pneumoniae (22%). Twenty-eight children underwent simple chest tube drainage and 26 underwent VATS. The variables age, history time and pH of the pleural fluid showed no significant differences. The drainage time was significantly lower in patients undergoing VATS (4.5 ± 1.8 days) (p < 0.001). The need for surgical approach was significantly higher in the group undergoing simple chest tube drainage (17.9%). Parapneumonic empyema chest drainage in children was more efficient in the group where there was VATS assistance, for being faster and not requiring another surgery in patient’s evolution

O empiema tem sido tratado de várias formas, desde a toracocentese seriada, drenagem torácica fechada (drenagem simples), drenagem com infusão de fibrinolíticos, descorticação por toracotomia e limpeza da cavidade e drenagem através da videotoracoscopia (CTVA). Apesar de a drenagem simples ser um método bastante antigo, é muito eficaz, dependendo do estágio do empiema. Já a CTVA, mesmo sendo mais invasiva, por demandar anestesia geral, é resolutiva na maioria dos estágios do empiema. Analisar os casos de empiema pleural parapneumônico em crianças submetidas à drenagem simples ou à videotoracoscopia precoce em nosso serviço para determinar quais são os fatores determinantes na evolução favorável do tratamento. Ensaio clínico controlado avaliando idade, gênero, queixa, tempo de diagnóstico, aspecto do líquido, patógenos encontrados, tipo de tratamento (drenagem torácica simples ou videotoracoscopia precoce), tempo de drenagem, necessidade de reintervenção, troca do antibiótico e tempo de internação. Foram analisados 54 pacientes com idade de sete meses a 10 anos, tratados no Serviço de Cirurgia Torácica do HCFMB UNESP, com diagnóstico de empiema pleural. O gênero masculino foi predominante (54%), o hemitórax mais acometido foi o direito (28 pacientes) e o tempo de história clínica variou de um a 30 dias. Trinta e dois pacientes foram tratados previamente com antibióticos e em 22% dos casos a bacterioscopia ou a cultura foram positivos para Streptococcus pneumoniae. Vinte e oito crianças foram submetidas à drenagem torácica simples e 26 a CTVA. As variáveis idade, tempo de história e pH do líquido pleural, não apresentaram diferenças significativas. No entanto, o tempo de drenagem foi significativamente menor nos pacientes submetidos à CTVA (4,5 ± 1,8 dias) (p<0,001). A necessidade de abordagem cirúrgica ocorreu somente no grupo submetido à drenagem torácica simples (17,9% p=0,02). A drenagem ...
Keywords: Empiema - Cirurgia; Pleura - Doenças; Toracoscopia; Diagnóstico por imagem; Crianças - Doenças - Tratamento; Pleura - Diseases